Aplicação de técnicas estatísticas na otimização e controle de qualidade de produtos para a indústria de compostos plásticos - Dalanesi, Luiz Antonio (2014)
This work aimed to apply statistical techniques in process control and product development in a company in the plastic industry branch. It s demonstrated the use of statistical process control in color quality control using colorimetric CIELAB coordinates in a thermoplastic compounds process for rotational molding, which was not introduced in the company. Moreover, describes the use of design of experiments in search of improved composition for compound mechanical properties optimization using nano carbonate, stearic acid and zinc stearate applied on linear low density polyethylene. For the analysis was used Pareto diagram, response surface graphs and process control graphs. The control charts showed that the process does not generate non-conforming products, and it is under statistic control. Capability indices indicate the process is not capable, so it necessary investigate the common causes using statistical tools to make it capable and optimize it. The design of experiments identified the global optimum condition reached with a maximum mix of nanocarbonato, stearic acid and zinc stearate.